Pengembangan Media Pembelajaran Moker (Mockup Materi Sumber Daya Alam) Untuk Siswa Kelas Iv Sekolah Dasar - Erliana Novita; Ilmawati Fahmi Imron; Endang Sri Mujiwati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to produce a product for the development of Moker Dalam learning media (Mockup of Natural Resources) for the natural resources module. The method in this study uses the R&D method with the ADDIE model consisting of five stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The procedures in this study include (1) analysis of performance and needs, (2) designing media designs, (3) developing media, (4) implementing or implementing media, (5) final evaluation of the developed media. The subjects in this study were teachers and fourth grade students at SDN 1 Karangtengah, Panggul District, Trenggalek Regency. The results showed that the development of Moker Dalam learning media was declared valid because it got a construction validation score of 87% and material validation got a score of 90%. The Moker Dalam learning media was also declared effective because it got a score of 88% in the limited trial and got a score of 90% in the wide trial. The results of the teacher's response to the Moker Dalam learning media are 91% and students 98.5%. Based on these results, Moker Dalam learning media can be said to be very valid, very effective and well used.